Determination of energy levels at the interface between O2 plasma treated ITO/P3HT : PCBM and PEDOT : PSS/P3HT : PCBM using angular-resolved x-ray and ultraviolet photoelectron spectroscopy - Whitcher, T.J.; Talik, N.A.; Woon, K.L.; Chanlek, N.; Nakajima, H.; Saisopa, T.; Songsiriritthigul, P. (Institute of Physics, 2014)
Interfacial energy alignments at the anode of solution processable organic photovoltaics are rarely studied. Here we use blended regio-regular poly(3-hexylthiophene) (P3HT) : phenyl-C61-butyric acid methyl ester (PCBM) deposited on top of O2 plasma cleaned indium tin oxide (ITO) and poly(3,4-ethylene-dioxythiophene) : polystyrene sulfonic acid (PEDOT : PSS) as a platform to obtain the interfacial energy alignment using angular-resolved x-ray and ultraviolet photoelectron spectroscopy. A strong downward vacuum level bending of 1.3 eV at the interface for plasma-ITO/P3HT : PCBM is observed. This results in an interfacial energetic barrier as high as 2.5 eV for holes and a reduction of barrier for electrons. This could be one of the contributing factors that result in lower device efficiency in O2 plasma-ITO/P3HT : PCBM compared to O2 plasma-ITO/PEDOT : PSS/P3HT : PCBM. The full interfacial energy diagram is determined for O2 plasma-ITO/P3HT : PCBM and PEDOT : PSS/P3HT : PCBM. Such methods can be extended to study various interfacial properties of solution processable organic semiconducting materials.